Modelling, Simulation of Permanent Magnet Synchronous Machine Drive using FOC Technique (Global Journals of Research in Engineering, 2013)
The research work deals with the detailed modeling of a permanent magnet synchronous motor drive system in Simulink Field oriented control is used for the operation of the drive The simulation includes all realistic components of the system This enables the calculation of currents and voltages in different parts of the inverter and motor under transient and steady conditions The losses in different parts are calculated facilitating the design of the inverter A closed loop control system with a Proportional Integral PI controller in the speed loop has been designed to operate in constant torque and flux weakening regions Implementation has been done in Simulink
Keywords: permanent magnet synchronous machine (PMSM); field oriented control (FOC); voltage source inverter (VSI)